Investigating the effects of IFNγ signalling on transcriptional, epigenetic and enhancer landscapes - Lamstaes, A (2021)
IFNγ signalling can have contradictory roles in a tumour microenvironment. Predominantly, IFNγ has an anti-tumour function, activating the immune system against the cancer. However, pro-tumour activities of IFNγ have also been observed. Its choice between the two opposing outcomes appears to be context dependent and the mechanism instructing this choice isn’t well understood. One prevailing determinant comes from the IFNγ-induced upregulation of PD-L1, an immunosuppressive ligand. Binding of PD-L1 to its receptor, PD-1, inhibits immune cells despite the presence of other activating signals, enabling cancer immune evasion. Increased knowledge of IFNγ-induced gene expression within cancer cells, including the regulation of PD-L1, would enable a more accurate prediction of IFNγ’s behaviour in the tumour microenvironment.